Reconstructing Legal Frameworks: Central-Local Government Collaboration during the Pandemic in Indonesia - Trubus Rahardiansah Prawiraharja (International Journal of Social Service and Research, 2023)
This research discusses the issue of centralization and decentralization in handling the COVID-19 pandemic, focusing on the Indonesian context. Criticism of decentralization in COVID-19 was conveyed by Smith (2012), who considered it a form of centralization that strengthens narrow interests and threatens the public interest. This research also looks at the implementation of health decentralization in Natuna, which is experiencing severe challenges such as a shortage of medical personnel, lack of timely available funds, and inadequate availability of vaccines and medical materials. In addition, the COVID-19 pandemic has raised challenges in coordinating and managing responses in various countries, with some adopting a centralized approach and others favoring decentralization. This research tries to explore the legal links between the central and regional governments in handling COVID-19 in Indonesia, with a focus on the impact of existing regulations such as Law No. 24 of 2007 concerning Disaster Management, Law No. 23 of 2014 concerning Regional Government, and Law no. 6 of 2018 concerning Health Quarantine regarding cooperation and coordination between the central and regional governments in handling the pandemic. This research is vital because COVID-19 is a global health crisis affecting various social, economic, and political aspects. With a better understanding of the legal relationship between central and regional governments in handling the pandemic, it is hoped that response coordination and effectiveness can be improved, thereby saving lives and reducing adverse social and economic impacts. This research has the advantage of focusing on the legal relationship between the central and regional governments in handling the COVID-19 pandemic in Indonesia and recommendations for reconstructing this legal relationship by referring to the 1945 Constitution. Good collaboration between the central and regional governments is considered vital in handling the COVID-19 pandemic -19 in the future.